PERANAN KOLOID Al DAN Fe AKTIF DALAM PROSES RETENSI FOSFAT PADA ANDISOLS DARI SUMATERA BARAT - Dian Fiantis (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2004)
The presence of active Al and Fe compounds in large amount in Andisols has caused strong P-retention on these mineral structure or it is bound on OH functional group or positively charged H. The objective of this research was to provide fundamental information to manage and conserve Andisols as used to be vegetable production centre in West Sumatra. The results showed that volcanic soil from Pasaman Mountain had higher retention capacity than that of Marapi Mountain. Therefore, it was needed more P for optimum plant growth. The most dominant soil properties affected pattern and amount of P retention was due to type of clay mineral found in volcanic soils. The dominant clay mineral on Andisols in West Sumatra was alofan and ferryhydrite (non-crystalline clay mineral) which are active component of Al and Fe colloids. Key Words: Volcanic ash soil, P retention, Alofan